Cardiovascular Diseases: Therapeutic Potential of SGLT-2 Inhibitors - Weronika Frąk; Joanna Hajdys; Ewa Radzioch; Magdalena Szlagor; Ewelina Młynarska; Jacek Rysz; Beata Franczyk (Biomedicines, 2023)
Cardiovascular diseases (CVD) are a global health concern, affecting millions of patients worldwide and being the leading cause of global morbidity and mortality, thus creating a major public health concern. Sodium/glucose cotransporter 2 (SGLT2) inhibitors have emerged as a promising class of medications for managing CVD. Initially developed as antihyperglycemic agents for treating type 2 diabetes, these drugs have demonstrated significant cardiovascular benefits beyond glycemic control. In our paper, we discuss the role of empagliflozin, dapagliflozin, canagliflozin, ertugliflozin, and the relatively recently approved bexagliflozin, the class of SGLT-2 inhibitors, as potential therapeutic targets for cardiovascular diseases. All mentioned SGLT-2 inhibitors have demonstrated significant cardiovascular benefits and renal protection in clinical trials, in patients with or without type 2 diabetes. These novel therapeutic approaches aim to develop more effective treatments that improve patient outcomes and reduce the burden of these conditions. However, the major scientific achievements of recent years and the many new discoveries and mechanisms still require careful attention and additional studies.